Reproductive disorders in male patients with epilepsy - G. N. Avakyan; O. L. Badalyan; E. V. Krikova; A. S. Chukanova; S. G. Burd (Эпилепсия и пароксизмальные состояния, 2016)
This article discusses the problem of impaired reproductive function and sexual health in male patients with epilepsy. Issues reviewed include the aetiology of these dysfunctions (most probably due to a variety of causes), epilepsy as such, as well as drugs used for its treatment; these issues are closely related to each other and have a considerable effect on the manifestations of this condition. Impairments of sex steroid concentrations, hypothalamic – pituitary function, as well as testicular function, form a basis for reproductive dysfunction in male patients with epilepsy. The psychosocial complications of epilepsy can have implications for reproductive health and sexual function. Practitioners should pay more attention to these problems, as patients frequently deny or fail to notice some of these disturbances.